The economic effects of exogenous fiscal shocks in Spain: a SVAR approach - Francisco de Castro Fernández; Pablo Hernández de Cos (European Central Bank (ECB), 2006)
This paper estimates the effects of exogenous fiscal policy shocks in Spain in a VAR framework. Government expenditure expansionary shocks are found to have positive effects on output in the short-term at the cost of higher inflation and public deficits and lower output in the medium and long term. Tax increases are found to drag economic activity in the medium term while entailing an only temporary improvement of the public budget balance. The application of these results to the analysis of fiscal policy in Spain since the mid-nineties points to the conclusion that the consolidation process does not seem to have involved costs in terms of output growth. Moreover, the stance of fiscal policy has become more counter-cyclical in that period.
Keywords: E62; H30; 330; Fiscal multipliers; Fiscal shocks; VAR; Finanzpolitik; Schock; VAR-Modell; Spanien